2019
DOI: 10.1109/access.2018.2888952
|View full text |Cite
|
Sign up to set email alerts
|

Revenue Model of Supply Chain by Internet of Things Technology

Abstract: Under the condition of elastic demand and different market scales, the optimization of multiproduct supply chain by the Internet of Things (IoT) technology was studied from the perspective of overall supply chain revenue in this paper. Particularly, the supply chain revenue model in a two-stage multi-product supply chain is established to analyze the impact of the IoT technology on the overall supply chain revenue. The imperialist competitive algorithm is introduced, and the algorithm is improved to solve the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Many previous studies have utilized IoT in two-level multi-product supply chains, concluding that the effective use of IoT can optimize multi-product supply chains. The authors demonstrated that the proper deployment of information processing leads to better information dissemination throughout the supply chain [31]. Tian in 2016 discussed the priority of developing and using RFID and blockchain technologies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many previous studies have utilized IoT in two-level multi-product supply chains, concluding that the effective use of IoT can optimize multi-product supply chains. The authors demonstrated that the proper deployment of information processing leads to better information dissemination throughout the supply chain [31]. Tian in 2016 discussed the priority of developing and using RFID and blockchain technologies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the basis of their power or the cost function, certain best among initial countries will be imperialists that begin taking control of the other countries (the colonies). Every colony is attracted to an imperialist that is based on the power [19]. The colonies for every imperialist is expressed as (1):…”
Section: Imperialist Competitive Algorithm (Ica)mentioning
confidence: 99%
“…Due to the rapid development of science and technology, the cost of data capture and storage has been reduced dramatically, which makes it easy to record each day's trading data related to the financial market. As a result, significant financial analysis of data has become a prominent area of research in economics and a variety of other disciplines [ 2 ].…”
Section: Introductionmentioning
confidence: 99%